Hydrolysis-resistant sheath material and photovoltaic cable
By connecting octamethylcyclotetrasiloxane into the sheath material of the photovoltaic cable and adding POE and hydrophobic modified basalt fibers, the problem of the photovoltaic cable sheath layer is easily swelling and hydrolyzing in humid environments, which significantly improves the hydrolysis resistance and service life of the material.
Patent Information
- Application Number
- CN202411913354.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-24
AI Technical Summary
The sheath layer of photovoltaic cables is prone to swelling and hydrolysis in humid or water-impregnated environments, resulting in reduced strength and easy damage, affecting service life and effect.
Using a hydrolysis-resistant sheathing material, including modified polyurethane elastomer, filler, POE and hydrophobic modified basalt fibers, is connected to the polymer chain of the modified polyurethane through octamethylcyclotetrasiloxane to enhance the hydrolysis resistance and toughness of the material.
It significantly improves the hydrolysis resistance, tensile strength and elongation of break of the sheath material, and extends the service life of photovoltaic cables in wet or water-impregnated environments.
Smart Images

Figure BDA0005206279320000061 
Figure BDA0005206279320000071
Abstract
Description
Technical Field
[0001] The present application relates to a cable, and in particular to a hydrolysis-resistant sheath material and a photovoltaic cable. Background Art
[0002] Solar power generation technology has become more popular and mature, and the solar photovoltaic grid-connected power generation industry has become one of the most popular emerging industries in the world today. With the development of the solar photovoltaic grid-connected power generation industry, the demand for land for solar photovoltaic grid-connected power generation has shifted the laying site to water or to more severe environmental conditions. Therefore, the photovoltaic cables used in solar photovoltaic grid-connected power generation often need to be exposed to the sun and rain, and even float on the water.
[0003] The sheath layer of the photovoltaic cable is in contact with and immersed in water for a long time, which is prone to swelling and hydrolysis, resulting in reduced strength of the sheath layer and easy damage, exposing the internal insulation layer or other components, affecting the service life and use effect of the photovoltaic cable. Summary of the invention
[0004] In order to extend the service life of a photovoltaic cable in a humid or water-soaked environment, a hydrolysis-resistant sheath material and a photovoltaic cable are provided.
[0005] The above first invention objective of the present invention is achieved through the following technical solutions: A hydrolysis-resistant sheath material, comprising the following raw materials in parts by weight: 60-80 parts of modified polyurethane elastomer, The filler is 10 to 20 parts, and the modified polyurethane is obtained by copolymerization of polyether polyol, diisocyanate, octamethylcyclotetrasiloxane and a chain extender through catalysis.
[0006] By adopting the above technical scheme, octamethylcyclotetrasiloxane is connected to the polymerization chain of modified polyurethane under the activation of diisocyanate and catalysis of catalyst, and the polyurethane elastomer is modified from the molecular polymerization chain. The hydrolysis resistance of the obtained modified polyurethane elastomer is significantly improved, and the hydrolysis resistance of the sheath material is improved, thereby extending the service life of the photovoltaic cable in a humid or water-immersed environment.
[0007] Optionally, the raw material of the sheath material also includes 10 to 12 parts of POE.
[0008] By adopting the above technical solution, POE is added to adjust and improve the tensile strength and elongation at break of the sheath material, and the anti-penetration ability of the sheath material is improved, thereby improving the hydrolysis resistance of the sheath material.
[0009] Optionally, the raw materials of the sheath material also include 3 to 5 parts of POE-g-MAH.
[0010] By adopting the above technical solution, POE-g-MAH is compounded with POE, and the compatibility of POE with modified polyurethane materials is improved, so that the tensile strength, elongation at break and hydrolysis resistance are better improved.
[0011] Optionally, the diisocyanate is diphenylmethane diisocyanate, and the polyether polyol is obtained by compounding polytetramethylene ether diol and polyoxypropylene ether diol.
[0012] By adopting the above technical solution, the obtained sheath material has better hydrolysis resistance, tensile strength and elongation at break.
[0013] Optionally, the mass ratio of the polyether polyol, diisocyanate and octamethylcyclotetrasiloxane is controlled to be 10:4:0.8.
[0014] By adopting the above technical solution, the sheath material obtained at this proportion has better hydrolysis resistance, tensile strength and elongation at break.
[0015] Optionally, the raw material of the sheath material also includes 11 to 14 parts of basalt fiber.
[0016] By adopting the above technical solution, basalt fiber can enhance the toughness of the sheath material.
[0017] Optionally, the basalt fiber is surface-hydrophobic modified.
[0018] By adopting the above technical scheme, basalt fiber can enhance the toughness of the sheath material, and the hydrophobically modified basalt fiber can enhance the tensile strength and tensile elongation at break of the sheath material, and can also enhance the hydrolysis resistance of the sheath material.
[0019] The above second invention objective of the present invention is achieved through the following technical solutions: A photovoltaic cable comprises an inner core, an insulating layer and a sheath layer, wherein the sheath layer is made of the above-mentioned hydrolysis-resistant sheath material.
[0020] In summary, this application has at least the following beneficial effects: 1. Octamethylcyclotetrasiloxane is connected to the polymer chain of modified polyurethane to modify the polyurethane elastomer from the molecular polymer chain. The hydrolysis resistance of the obtained modified polyurethane elastomer is significantly improved, and the hydrolysis resistance of the sheath material is improved, thereby extending the service life of the photovoltaic cable in a humid or water-infiltrated environment; 2. Basalt fiber can enhance the toughness of the sheath material. The hydrophobically modified basalt fiber can enhance the tensile strength and elongation at break of the sheath material, and can also enhance the hydrolysis resistance of the sheath material. DETAILED DESCRIPTION
[0021] raw material Polytetramethylene glycol is PTMG 1000, a commercial product of Mitsubishi Chemical Corporation of Japan.
[0022] The polyoxypropylene ether glycol is PPG 1000, a commercially available product of Green Union (Jining) Chemical Technology Co., Ltd.
[0023] Diphenylmethane diisocyanate, isophorone diisocyanate, octamethylcyclotetrasiloxane, 1,4-butanediol, sodium methoxide, hexadecyltrimethoxysilane, and dibutyltin dilaurate are all commercially available industrial-grade raw materials.
[0024] The basalt fiber is 10 mm long and 0.1 μm in diameter.
[0025] The filler is light calcium carbonate, which is a commercially available product.
[0026] POE is Dow ENGAGE POE 8150 from the United States.
[0027] POE-g-MAH is Dow GR216 Preparation Example 1 A modified polyurethane elastomer, the raw materials of which include polyether polyol, diisocyanate, octamethylcyclotetrasiloxane and chain extender.
[0028] The polyether polyol is a compound of polytetramethylene ether glycol and polyoxypropylene ether glycol in a mass ratio of 1:0.6.
[0029] The diisocyanate is dibenzylmethane diisocyanate.
[0030] The chain extender is 1,4-butanediol.
[0031] The specific preparation process is as follows: Divide 9.6 kg of polyether polyol into group A polyether polyol and group B polyether polyol, wherein the mass ratio of group A polyether polyol to group B polyether polyol is 6:4; Heat the polyether polyol of group A to 68°C, add 0.9kg of diisocyanate, stir rapidly to mix, the temperature of the material to be stirred and mixed rises at a rate of less than 2°C / min, adjust the temperature to 80±1°C, and continue the reaction for 1h to obtain a transition reaction material; add 0.92kg of octamethylcyclotetrasiloxane and 0.01kg of sodium methoxide to the transition reaction material, control the temperature to 85±1°C, continue the reaction for 2h, and then evacuate to obtain a prepolymer; The polyether polyol of group B, 4.08 kg of chain extender, and 0.02 kg of dibutyltin dilaurate are mixed to obtain a mixture; After the prepolymer and the mixed material are heated to 60° C., they are quickly mixed at a rotation speed of 1200 r / min to be uniformly mixed, and extruded and granulated to obtain a polyurethane elastomer.
[0032] Preparation Example 2 A modified polyurethane elastomer, which is different from Preparation Example 1 in that the amount of octamethylcyclotetrasiloxane used in the preparation process is 0.4 kg.
[0033] Preparation Example 3 A modified polyurethane elastomer, which is different from Preparation Example 1 in that 1.35 kg of octamethylcyclotetrasiloxane is used in the preparation process.
[0034] Preparation Example 4 A modified polyurethane elastomer, which is different from Preparation Example 1 in that the diisocyanate is isophorone diisocyanate.
[0035] Preparation Example 5 A modified polyurethane elastomer, which is different from Preparation Example 1 in that the polyether polyol is a single polytetramethylene ether diol.
[0036] Preparation Example 6 A polyurethane elastomer is obtained by copolymerizing polyether polyol and diisocyanate.
[0037] The polyether polyol is a compound of polytetramethylene ether glycol and polyoxypropylene ether glycol in a mass ratio of 1:0.6.
[0038] The diisocyanate is dibenzylmethane diisocyanate.
[0039] The specific preparation process is as follows: Divide 9.6 kg of polyether polyol into group A polyether polyol and group B polyether polyol, wherein the mass ratio of group A polyether polyol to group B polyether polyol is 6:4; Heat the polyether polyol of group A to 68°C, add 0.9kg of diisocyanate, stir rapidly to mix, the temperature of the material to be stirred and mixed rises at a rate of less than 2°C / min, adjust the temperature to 80±1°C, continue the reaction for 3h, and then evacuate to obtain a prepolymer; The polyether polyol of group B, 4.08 kg of chain extender, and 0.02 kg of dibutyltin dilaurate are mixed to obtain a mixture; After the prepolymer and the mixed material are heated to 60° C., they are quickly mixed at a rotation speed of 1200 r / min to be uniformly mixed, and extruded and granulated to obtain a polyurethane elastomer.
[0040] Preparation Example 7 The invention discloses a hydrophobic modified basalt fiber, which is obtained by modifying the basalt fiber with hexadecyltrimethoxysilane.
[0041] The specific modification process is as follows: Basalt fiber, hexadecyltrimethoxysilane and methanol were stirred and mixed uniformly in a mass ratio of 100:12:4, and hydrophobically modified basalt fiber was obtained after methanol was evaporated and removed.
[0042] Example 1 A hydrolysis-resistant sheath material, whose raw materials are modified polyurethane elastomer, filler, POE, POE-g-MAH and hydrophobically modified basalt fiber.
[0043] The modified polyurethane elastomer was prepared in Preparation Example 1.
[0044] The hydrophobically modified basalt fiber was prepared in Preparation Example 7.
[0045] The specific preparation process is as follows: 75 kg of modified polyurethane elastomer, 17 kg of filler, 11.3 kg of POE, 4.5 kg of POE-g-MAH and 12 kg of hydrophobically modified basalt fiber were uniformly mixed to obtain a mixed raw material; The mixed raw materials are sent to a screw extruder for melting and mixing, and then extruded to a molding machine for molding on the outside of the cable.
[0046] If preparing the test sample, the mixed raw materials are sent to a screw extruder for melting and mixing, and then injected into a sample mold, and the sample is obtained after cooling.
[0047] Example 2 A hydrolysis-resistant sheath material, which is different from Example 1 in that the modified polyurethane elastomer is prepared according to Preparation Example 2.
[0048] Example 3 A hydrolysis-resistant sheath material, which is different from Example 1 in that the modified polyurethane elastomer is prepared according to Preparation Example 3.
[0049] Example 4 A hydrolysis-resistant sheath material, which is different from Example 1 in that the modified polyurethane elastomer is prepared according to Preparation Example 4.
[0050] Example 5 A hydrolysis-resistant sheath material, which is different from Example 1 in that the modified polyurethane elastomer is prepared according to Preparation Example 5.
[0051] Example 6 A hydrolysis-resistant sheath material, which is different from Example 1 in that its raw materials are modified polyurethane elastomer, filler and hydrophobically modified basalt fiber.
[0052] The specific preparation method is as follows: 75 kg of modified polyurethane elastomer, 17 kg of filler, 0.6 kg of antioxidant, 0.4 kg of UV inhibitor and 12 kg of hydrophobic modified basalt fiber were uniformly mixed to obtain a mixed raw material. The mixed raw materials are sent to a screw extruder for melting and mixing, and then extruded to a molding machine for molding on the outside of the cable.
[0053] If preparing the test sample, the mixed raw materials are sent to a screw extruder for melting and mixing, and then injected into a sample mold, and the sample is obtained after cooling.
[0054] Example 7 A hydrolysis-resistant sheath material, which is different from Example 1 in that its raw materials are modified polyurethane elastomer, filler, POE and hydrophobically modified basalt fiber.
[0055] The specific preparation method is as follows: 75 kg of modified polyurethane elastomer, 17 kg of filler, 0.6 kg of antioxidant, 0.4 kg of UV inhibitor, 11.3 kg of POE and 12 kg of hydrophobically modified basalt fiber were uniformly mixed to obtain a mixed raw material. The mixed raw materials are sent to a screw extruder for melting and mixing, and then extruded to a molding machine for molding on the outside of the cable.
[0056] If preparing the test sample, the mixed raw materials are sent to a screw extruder for melting and mixing, and then injected into a sample mold, and the sample is obtained after cooling.
[0057] Example 8 A hydrolysis-resistant sheath material, which is different from Example 1 in that its raw materials are modified polyurethane elastomer, filler, POE and POE-g-MAH.
[0058] The specific preparation method is as follows: 75 kg of modified polyurethane elastomer, 17 kg of filler, 0.6 kg of antioxidant, 0.4 kg of UV inhibitor, 11.3 kg of POE and 4.5 kg of POE-g-MAH were uniformly mixed to obtain a mixed raw material. The mixed raw materials are sent to a screw extruder for melting and mixing, and then extruded to a molding machine for molding on the outside of the cable.
[0059] If preparing the test sample, the mixed raw materials are sent to a screw extruder for melting and mixing, and then injected into a sample mold, and the sample is obtained after cooling.
[0060] Example 9 A hydrolysis-resistant sheath material, which is different from Example 1 in that its raw materials are modified polyurethane elastomer, filler, POE, POE-g-MAH and basalt fiber.
[0061] The specific preparation method is as follows: 75 kg of modified polyurethane elastomer, 17 kg of filler, 0.6 kg of antioxidant, 0.4 kg of UV inhibitor, 11.3 kg of POE, 4.5 kg of POE-g-MAH and 12 kg of basalt fiber were uniformly mixed to obtain a mixed raw material. The mixed raw materials are sent to a screw extruder for melting and mixing, and then extruded to a molding machine for molding on the outside of the cable.
[0062] If preparing the test sample, the mixed raw materials are sent to a screw extruder for melting and mixing, and then injected into a sample mold, and the sample is obtained after cooling.
[0063] Example 10 A hydrolysis-resistant sheath material, which differs from Example 1 in that the amounts of raw materials used are different, specifically: 60 kg of modified polyurethane elastomer, 10 kg of filler, 11.3 kg of POE, 4.5 kg of POE-g-MAH and 12 kg of hydrophobically modified basalt fiber.
[0064] Embodiment 11 A hydrolysis-resistant sheath material, which differs from Example 1 in that the amounts of raw materials used are different, specifically: 80 kg of modified polyurethane elastomer, 20 kg of filler, 12 kg of POE, 5 kg of POE-g-MAH and 14 kg of hydrophobically modified basalt fiber.
[0065] Comparative Example 1 A sheath material, which differs from Example 1 in that the modified polyurethane elastomer prepared in Preparation Example 1 is replaced by an equal mass of the polyurethane elastomer prepared in Preparation Example 6.
[0066] The tensile strength, elongation at break and the rate of change of properties after simulated hydrolysis were tested for Examples 1 to 11 and Comparative Example 1.
[0067] The tensile strength test was carried out according to ASTM-D412.
[0068] The elongation at break test was carried out according to ASTM-D412.
[0069] The performance retention rate after simulated hydrolysis was tested by preparing the tensile strength and elongation at break tests according to ASTM-D412, and soaking it in deionized water at 70°C for 168 hours. After soaking, the samples were taken out and the surface moisture was dried, and then the tensile strength and elongation at break after simulated hydrolysis were tested according to ASTM-D412, and the tensile strength retention rate and elongation at break retention rate were calculated.
[0070] Tensile strength retention rate = tensile strength after simulated hydrolysis / tensile strength × 100%.
[0071] Retention rate of elongation at break = elongation at break after simulated hydrolysis / elongation at break × 100%.
[0072] The test results are shown in Table 1.
[0073] Table 1. Test results of Examples 1 to 11 and Comparative Example 1 Combined with Table 1, by comparing Example 1 with Comparative Example 1, it can be seen that the tensile strength and elongation at break of Example 1 are better than those of Comparative Example 1, and the tensile strength retention rate and elongation at break retention rate of Example 1 after simulated hydrolysis are significantly better than those of Comparative Example 1. The sheath material of Example 1 has better hydrolysis resistance than the sheath material of Comparative Example 1.
[0074] The sheath material of Example 1 adds a catalyst and octamethylcyclotetrasiloxane during the polymerization process of the polyurethane elastomer, and the octamethylcyclotetrasiloxane is ring-opened and connected to the polymerization chain of the modified polyurethane under the activation of diisocyanate, so that the polyurethane elastomer is modified from the molecular polymerization chain. The hydrolysis resistance of the obtained modified polyurethane elastomer is significantly improved, and the hydrolysis resistance of the sheath material is improved, thereby extending the service life of the photovoltaic cable in a humid or water-infiltrated environment.
[0075] Combined with Examples 1 to 3, the access of octamethylcyclotetrasiloxane to the polymer chain of modified polyurethane will enhance the hydrolysis resistance of the modified polyurethane elastomer, and will also affect the tensile strength and tensile fracture rate of the modified polyurethane elasticity. Comparing the test results of Examples 1 to 3, it can be seen that the tensile strength retention rate and elongation at break retention rate of Examples 1 and 3 are better than those of Example 2, and the tensile strength and elongation at break of Example 1 are the best among Examples 1 to 3. Therefore, when octamethylcyclotetrasiloxane is accessed to the polymer chain of modified polyurethane, the tensile strength and elongation at break of the sheath material increase first and then decrease as the access amount increases. Therefore, in this application, the modified polyurethane elasticity is preferably controlled to have a mass ratio of 10:4:0.8 for polyether polyol, diisocyanate, and octamethylcyclotetrasiloxane.
[0076] By comparing Example 1 with Examples 4 to 5, it can be seen that the polyether polyol used in Example 4 is different from that in Example 1, and the diisocyanate used in Example 5 is different from that in Example 1. In the test results, the tensile strength and elongation at break of Example 1 are greater than those of Examples 4 to 5, and the tensile strength retention rate and elongation at break retention rate of Example 1 are both greater than those of Examples 4 to 5. It can be seen that in the present application, it is better to use polytetramethylene ether diol and polyoxypropylene ether diol as the polyether polyol, and it is better to use diphenylmethane diisocyanate as the diisocyanate.
[0077] By comparing Example 1 with Examples 6 to 7, it can be seen that the raw materials of Example 1 include POE and POE-g-MAH, POE and POE-g-MAH are not added to the raw materials of Example 6, and only POE is added to the raw materials of Example 7 without POE-g-MAH. In the test results, the tensile strength and elongation at break of Example 7 are greater than those of Example 6, and the tensile strength retention rate and elongation at break of Example 7 are greater than those of Example 6. The tensile strength and elongation at break of Example 1 are greater than those of Example 7, and the tensile strength retention rate and elongation at break retention rate of Example 1 are greater than those of Example 7. Therefore, the addition of POE to the sheath material of the present application can enhance the hydrolysis resistance of the sheath material, and the addition of POE-g-MAH on the basis of the addition of POE can improve the compatibility of POE in the modified polyurethane elastomer, make the POE mixing more sufficient, and further improve the strength and hydrolysis resistance of the sheath material.
[0078] Comparing Example 1 with Examples 8 to 9, the raw materials of Example 1 include the hydrophobically modified basalt fiber prepared in Preparation Example 7, the raw materials of Example 8 do not contain unmodified basalt fiber or hydrophobically modified basalt fiber, and the raw materials of Example 9 contain unmodified basalt fiber. In the test results, the tensile strength of Example 9 is significantly greater than that of Example 8, and the elongation at break of Example 9 is greater than that of Example 8. Therefore, adding basalt fiber to the sheath material can improve the tensile properties of the sheath material.
[0079] At the same time, the tensile strength and elongation at break of Example 1 are significantly greater than those of Example 9, and the improvement in the tensile strength retention rate and elongation at break of Example 1 compared with Example 9 is significantly better than the improvement in the tensile strength retention rate and elongation at break of Example 9 compared with Example 8. Therefore, hydrophobic modification of the basalt fiber added to the sheath material can further improve the tensile properties of the sheath material, and can also significantly improve the hydrolysis resistance of the sheath material.
[0080] In addition to Example 1, the present application also has other preferred examples found during the research process, such as Examples 10-11. In the test results, the tensile strength and elongation at break of Examples 10-11 are better than those of Comparative Example 1, and the tensile strength retention rate and elongation at break retention rate of Examples 10-11 after simulated hydrolysis are significantly better than those of Comparative Example 1. The sheath materials of Examples 10-11 have better hydrolysis resistance than the sheath material of Comparative Example 1.
[0081] Example 12 A photovoltaic cable comprises, from outside to inside, a sheath layer, an insulating layer, and an inner core, wherein the sheath layer is made of a sheath material, and the sheath material is one of embodiments 1 to 11.
[0082] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed. However, as long as the modifications are within the scope of protection required by the present application, they shall be protected by the patent law.
Claims
1. A hydrolysis-resistant sheath material, characterized in that: Including the following raw materials by mass: 60~80 parts of modified polyurethane elastomer, 10~20 parts of filler, The modified polyurethane is obtained by catalytic copolymerization of polyether polyol, diisocyanate, octamethylcyclotetrasiloxane and a chain extender.
2. A hydrolysis-resistant sheath material according to claim 1, characterized in that: The raw materials of the sheath material also include 10 to 12 parts of POE.
3. A hydrolysis-resistant sheath material according to claim 2, characterized in that: The raw materials of the sheath material also include 3 to 5 parts of POE-g-MAH.
4. The hydrolysis-resistant sheath material according to claim 1, characterized in that: The diisocyanate is diphenylmethane diisocyanate, and the polyether polyol is obtained by compounding polytetramethylene ether diol and polyoxypropylene ether diol.
5. A hydrolysis-resistant sheath material according to claim 4, characterized in that: The mass ratio of the polyether polyol, diisocyanate and octamethylcyclotetrasiloxane is controlled to be 10:4:0.
8.
6. The hydrolysis-resistant sheath material according to claim 1, characterized in that: The raw materials of the sheath material also include 11 to 14 parts of basalt fiber.
7. The hydrolysis-resistant sheath material according to claim 1, characterized in that: The basalt fiber is surface-hydrophobic modified.
8. A photovoltaic cable, characterized in that: The invention comprises an inner core, an insulating layer and a sheath layer, wherein the sheath layer is made of the hydrolysis-resistant sheath material according to any one of claims 1 to 7.
Citation Information
Patent Citations
High-light-transmittance TPU film and preparation method thereof
CN110922562A